Adaptive noise Wiener filter for scanning electron microscope imaging system. Issue 2 (31st July 2015) - Sim, K. S.; Teh, V.; Nia, M. E.
Summary: Noise on scanning electron microscope (SEM) images is studied. Gaussian noise is the most common type of noise in SEM image. We developed a new noise reduction filter based on the Wiener filter. We compared the performance of this new filter namely adaptive noise Wiener (ANW) filter, with four common existing filters as well as average filter, median filter, Gaussian smoothing filter and the Wiener filter. Based on the experiments results the proposed new filter has better performance on different noise variance comparing to the other existing noise removal filters in the experiments. SCANNING 38:148–163, 2016. © 2015 Wiley Periodicals, Inc.